Dual-time-point FDG-PET/CT Imaging of Temporal Bone Chondroblastoma: A Report of Two Cases - Toriihara, Akira (Asia Ocean J Nucl Med Biol, 2015)
Temporal bone chondroblastoma is an extremely rare benign bone tumor. We encountered two cases showing similar imaging findings on computed tomography (CT), magnetic resonance imaging (MRI), and dual-time-point (18)F-fluorodeoxyglucose ((18)F-FDG) positron emission tomography (PET)/CT. In both cases, CT images revealed temporal bone defects and sclerotic changes around the tumor. Most parts of the tumor showed low signal intensity on T2-weighted MRI images and non-uniform enhancement on gadolinium contrast-enhanced T1-weighted images. No increase in signal intensity was noted in diffusion-weighted images. Dual-time-point PET/CT showed markedly elevated (18)F-FDG uptake, which increased from the early to delayed phase. Nevertheless, immunohistochemical analysis of the resected tumor tissue revealed weak expression of glucose transporter-1 and hexokinase II in both tumors. Temporal bone tumors, showing markedly elevated (18)F-FDG uptake, which increases from the early to delayed phase on PET/CT images, may be diagnosed as malignant bone tumors. Therefore, the differential diagnosis should include chondroblastoma in combination with its characteristic findings on CT and MRI.